Governance Quality, Fairness Perceptions, and Satisfaction with Democracy in Latin America. (May 2021) - Saxton, Gregory W.
ABSTRACT: How do individuals' fairness judgments aﬀect their political evaluations? This article argues that when citizens perceive high levels of distributive unfairness in society, they will be less satisfied with the way democracy functions. Yet good governance—that is, impartiality in the exercise of political authority—should mitigate the negative inﬂuence of perceived distributive unfairness on satisfaction. Using a cross-national analysis of 18 Latin American countries from 2011 to 2015, this study demonstrates that individuals are significantly less satisfied with democracy when they perceive their country's income distribution as unfair. Yet good governance significantly oﬀsets this negative relationship, even in a region with the highest level of inequality in the world. These findings imply that policymakers can bolster democratic satisfaction, even in places where citizens perceive the income distribution as fundamentally unfair, by committing to good governance and fair democratic procedures.